Persepsi Guru terhadap Pelaksanaan Kurikulum Merdeka Belajar di SMA Negeri 3 Padang - Afifah, Syifa; Zuwirna, Zuwirna; Amsal, Mutiara Felicita; Pratiwi, Rahmi; Fitriani, Aura Syfa; Alifa, Zaqiya Zahwa (Universitas Negeri Padang, 2025)
The Merdeka Curriculum is a curriculum with diverse intracurricular learning, the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. The purpose of this study was to determine teacher perceptions of the Merdeka Curriculum at SMA Negeri 3 Padang, namely planning, implementation and evaluation processes. This research is a quantitative descriptive study using population research. Sampling using the total sampling technique with 65 respondents who implemented the Merdeka Curriculum at SMA Negeri 3 Padang. The data collection technique used in this study was a questionnaire. The validity test of the research instrument is based on logical validity and emipirs while the reliability test uses the Cronbach's Alpha technique with a reliability coefficient value> 0.7. The results of this study indicate that: (1) teachers' perceptions of the Merdeka Curriculum in SMA Negeri 3 Padang are in the well implemented category (97%); (2) teachers' perceptions of the preparation of the Merdeka Curriculum in SMA Negeri 3 Padang are in the very well implemented category (97%); (3) teachers' perceptions of the implementation of the Merdeka Curriculum learning in SMA Negeri 3 Padang are in the well implemented category (95.4%); (4) teachers' perceptions of the Merdeka Curriculum assessment process in SMA Negeri 3 Padang are in the very well implemented category (84.6%).